Storyworlds: the lake of stars - Gavin, Jamila; Mayo, Diana (Heinemann UK, 1996)
Part of the "Storyworlds" series, this is a pack of the four Stage Five traditional tales. Each story reinforces between 20 and 40 new words, and adopts a broadening approach, to encourage the move to independent reading. Continued repetition of text should help to build the child's confidence.